Paisagens polifônicas da música na escola: saberes e práticas docentes - Beaumont, Maria Teresa de (2003)
This research has as general objective to analyze the know them and educational practices developed in the teaching process and learning of Music, in schools of the public and private net, in the Infantile Education and initial series of the Fundamental Teaching. Through the thematic oral history as research methodology, ﬁve interviews were accomplished. Three of them were accomplished with teachers of the Infantile Education and initial series of the Fundamental Teaching. The other ones two were accomplished with a music teachers. The oral sources were complemented with written sources, such as the official documents of the education system: LDB n. 9.394/96, Referencial Curricular Nacional for the Infantile Education — RCNs and Parâmetros Curriculares Nacionais - PCNs, as well as the bibliographical collection of the areas of Education and Musical Education. The landscapes woven through the narratives they are conﬁgured as replete tissues of multiple composed sonorities for teachers and teachers of Music. Inside this plot we positioned ourselves in direction to the understanding of the teaching non formal and formal/disciplinar of Music in the schools, with the expectation that teachers and specialists can work this way area integrated into the other areas of the school knowledge. We positioned ourselves in direction to the need that the musical formation is inserted in the current context of critical reflection and of proposed consistent of educational formation, initial and continuous of teachers. Reinforced the importance that those courses know, enlarge and deepen so much the know them that those professionals possess, as the practices that carry out with Music. We reiterated that plot among the know and practices are interpreted at the schools by teachers, teachers of Music, children, parents, direction teams and Municipal and State Clerkships of Education, The debates on that thematic one are accomplished by all the professionals involved with the Infantile Education and initial series of the Fundamental Teaching.